Analisis Pengaruh Kepemilikan Blockholder, Kepemilikan Manajerial, Kepemilikan Institusional, dan Komite Audit terhadap Nilai Perusahaan - Wirawardhana, Iwan; Sitardja, Meco (School of Accountancy, University of Agung Podomoro, 2018)
The aim of this study is to analyse the effect of Blockholder Ownership, Managerial Ownership,Institutional Ownership, and Audit Committee towards Firm Value. The background of this research isthe agency theory and ownership theory. The population in this study are 46 property companies listedon the Indonesia Stock Exchange (IDX) for the period 2012-2016. By using purposive samplingtechnique, 35 companies are qualified as data samples. This research uses the random effect model asthe estimation model and multiple regression as the method of analysis. The results of this study showsthat Institutional Ownership has a positive effect on Firm Value. Meanwhile, Blockholder Ownership,Managerial Ownership, and Audit Committee have no effect on Firm Value. Moreover, the F-testimplies that the variables, blockholder ownership, managerial ownership, institutional ownership, andaudit committee, simultaneously influence firm value.